The substrate, a key factor or not, to explain the species diversity of diatom communities in mineral springs. Issue 2 (3rd April 2022) - Baker, Lory-Anne; Biron, David G.; Millan, Fanny; Voldoire, Olivier; Breton, Vincent; Allain, Elisabeth; Wetzel, Carlos E.; Ector, Luc; Beauger, Aude
ABSTRACT: Diatoms colonised most aquatic ecosystems on earth from marine to freshwater ones, and also the springs containing a fairly large and poorly known diversity of diatoms. While investigations on the influence of substrates on diatom assemblages in rivers are relatively well documented, few studies have been done for mineral springs. The purpose of this study was to analyse if the type of substrate on which diatoms grow, influences diatom assemblage's ecological metrics (i.e. species richness, diversity and evenness) and diatom composition. During 18 months, two minerals springs of Auvergne (France), La Montagne and Mariol were sampled monthly, both epilithic and epipelic diatom communities. A total of 201 taxa were found. Data analysis showed that location (i.e. environmental variables of a site) explained significantly higher portions of variability of diatom composition than substrate. However, substrate have a role in the species abundances as much as the location.